Characterization And Performance Evaluation Of Metal Organic Framework For Carbon Dioxide Gas Adsorption - Ho, Pui San (2020)
Concerns about the global warming issue have directed to substantial interest in removing the carbon dioxide (CO2) gas from flue gas or atmosphere. CO2 sequestration with selective adsorption is an effective established carbon dioxide gas removal approaches due to its easy operation, low energy requirement and tunable selectivity. A new type of nano-porous materials known as metal-organic frameworks (MOF), which has gas adsorption capability with unprecedented high porosity and high loading capacity is developed as a new promising candidate for CO2 gas capture. In this study, MIL-101 (Cr) MOF samples were fabricated under different crystallization time and loading of organic acid using chromium (III) nitrate nonahydrate (Cr(NO3)3.9H2O) and benzene-1,4-dicarboxylic acid (BDC) while UiO66 (Ce) MOF samples were synthesized under different loading of organic acid and modulator using cerium ammonium nitrate (CAN) and benzene-1,4-dicarboxylic acid (BDC). Both types of MOF samples will be fabricated by using solvent-free method (mechanochemical). The XRD results indicated that the fabricated MIL-101 (Cr) MOFs were well agreed with the literature studies with the similar 2θ peak observed in the analysis. The morphology of the MIL-101 (Cr) MOF with the Cr/BDC molar ratio of 1 to 1 and crystallization time of 4 hours (MIL-101(Cr)-1-4) captured by SEM illustrated the dispersion of small irregular granular shaped particles. The EDX analysis result revealed that the Cr element was successfully incorporated into all the fabricated MIL-101 (Cr) MOF in regardless of the ratio of Cr to BDC and crystallization time. Carboxylic organic linker that participated the reaction was the source for the existence of C atom and O atom within the samples. The FTIR spectra of the synthesized MIL-101 (Cr) MOFs suggested the spectrum are well corresponding with that reported in the literature, especially for the fingerprint region. Hence, this confirming the formation of MIL-101(Cr) MOF. An intense absorption band was observed at 1390cm-1 due to symmetric (O-C-O) vibration of the benzene ring. While the moderate intensity of absorption band observed at wavenumber of 720 cm-1 is attributed to mono-substituted benzene ring. The CO2 gas adsorption result exhibited that the MIL-101(Cr)-1-4 yield the highest adsorption capacity at 18.7772 mmol/g, suggested that the MIL-101(Cr) sample with vi the Cr/BDC molar ratio of 1:1 and crystallization time of 4 hours exhibits good CO2 gas adsorption performance.